2008
DOI: 10.1007/s00520-008-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

The religiousness as a way of coping with anxiety in women with breast cancer at different disease stages

Abstract: The obtained results allow us to conclude that: (a) religiousness is an effective factor of coping with anxiety only of the end-stage breast cancer patients; (b) cancer stage is a differentiating factor in respect of revealed anxiety level in study subjects; (c) exacerbation of somatic symptoms does not influence the anxiety level in terminal cancer patients and at disease-free period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…(18) In another study, the anxiety level assessed by the Trait Anxiety Inventory-State Scale was correlated with the religiousness of Personal and Rotterdam Symptom Checklist in 180 women with breast cancer. (19) The results showed that: religiosity is a factor for effectively coping and dealing with the anxiety of patients with terminal breast cancer, the stage of cancer is a differentiating factor compared to levels of anxiety revealed in the subjects studied; exacerbation of somatic symptoms did not influence the level of anxiety in terminal cancer patients and diseases without period.…”
Section: Discussionmentioning
confidence: 85%
“…(18) In another study, the anxiety level assessed by the Trait Anxiety Inventory-State Scale was correlated with the religiousness of Personal and Rotterdam Symptom Checklist in 180 women with breast cancer. (19) The results showed that: religiosity is a factor for effectively coping and dealing with the anxiety of patients with terminal breast cancer, the stage of cancer is a differentiating factor compared to levels of anxiety revealed in the subjects studied; exacerbation of somatic symptoms did not influence the level of anxiety in terminal cancer patients and diseases without period.…”
Section: Discussionmentioning
confidence: 85%
“…Research on quality of life following a cancer trajectory is an area of growing interest in Poland (Janiszewska et al, 2008;Osmanska, Borlowska, & Makarewicz, 2010;Rzewnicki & Jackiewicz, 2009;Wierzbicka, Kusnierkiewicz, Wojtowica, Maune, & Szyfter, 2001;Wronska, 2003). As psychosocial issues among r patients who survive cancer becomes an area of greater interest, we believe it important to this study results to describe the impact of having cancer and cancer treatment had on purpose of life and hope, among a sample of patients treated in Warsaw, Poland.…”
Section: Introduction Study Setting In Polandmentioning
confidence: 99%
“…Prevalence rates of anxiety disorders range from 0.9% to 49% in cancer populations . Although several studies focus on anxiety after the diagnosis of cancer and during the further course of the disease , to date little is known about the nonpsychiatric part of anxiety: a realistic reaction of fear to a threatening life event. One concept regarding the fear of recurrence and progressive course of chronic diseases is fear of disease progression (FoP) .…”
Section: Introductionmentioning
confidence: 99%